2017
DOI: 10.1038/s41598-017-11609-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of bacterial and fungal communities in Marcha and Thiat, traditionally prepared amylolytic starters of India

Abstract: Marcha and thiat are traditionally prepared amylolytic starters use for production of various ethnic alcoholic beverages in Sikkim and Meghalaya states in India. In the present study we have tried to investigate the bacterial and fungal community composition of marcha and thiat by using high throughput sequencing. Characterization of bacterial community depicts phylum Proteobacteria is the most dominant in both marcha (91.4%) and thiat (53.8%), followed by Firmicutes, and Actinobacteria. Estimates of fungal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 44 publications
5
36
1
Order By: Relevance
“…Khekhrii of Nagaland is prepared by naturally fermenting sprouted-rice grains and then sun-dried to use as dry starter culture to prepare zutho , local alcoholic beverage. Some species of yeasts Saccharomycopsis fibuligera, S. capsularis, Pichia anomala, P. burtonii, P. guilliermondii, P. fabianii, Trichosporon sp., Candida tropicalis, C. parapsilosis, C. montana, C. glabrata, Torulaspora delbrueckii, Saccharomyces cerevisiae, S. bayanus , and Wickerhamomyces anomalus were previously reported from some samples of marcha and hamei of India ( Hesseltine and Kurtzman, 1990 ; Tamang and Sarkar, 1995 ; Tsuyoshi et al, 2005 ; Jeyaram et al, 2008 , 2011 , Sha et al, 2016 , 2017 ).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Khekhrii of Nagaland is prepared by naturally fermenting sprouted-rice grains and then sun-dried to use as dry starter culture to prepare zutho , local alcoholic beverage. Some species of yeasts Saccharomycopsis fibuligera, S. capsularis, Pichia anomala, P. burtonii, P. guilliermondii, P. fabianii, Trichosporon sp., Candida tropicalis, C. parapsilosis, C. montana, C. glabrata, Torulaspora delbrueckii, Saccharomyces cerevisiae, S. bayanus , and Wickerhamomyces anomalus were previously reported from some samples of marcha and hamei of India ( Hesseltine and Kurtzman, 1990 ; Tamang and Sarkar, 1995 ; Tsuyoshi et al, 2005 ; Jeyaram et al, 2008 , 2011 , Sha et al, 2016 , 2017 ).…”
Section: Introductionmentioning
confidence: 98%
“…Ethnic people practicing the age-old traditional preservation or sub-culturing amylolytic and alcohol-producing as well as flavor-enhancing fungi and bacteria have attracted many researchers to study the microbial diversity in such starters. In recent years, few researchers have reported the fungal and bacterial species using both culture-dependent and-independent techniques in some common starter cultures of Asia such as marcha of India ( Tsuyoshi et al, 2005 ; Sha et al, 2017 ), daqua of China ( Wang et al, 2008 ; Zheng et al, 2012 ; Lv et al, 2013 ; Chen et al, 2014 ; Xu et al, 2017 ), benh men of Vietnam ( Dung et al, 2007 ; Thanh et al, 2008 ); nuruk of Korea ( Jung et al, 2012 ), and dombea of Cambodia ( Ly et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microbes have a very complex role in cereal fermentation and involves mixed cultures of yeasts, bacteria and fungi (Das et al 2014). A study on Marcha and Thiat, a starter cake used for the preparation of alcoholic beverage in Sikkim and Meghalaya states in India showed that proteobacteria was a dominant phylum followed by Firmicutes and Actinobacteria (Sha et al 2017). A study showed that succession of moulds and yeasts followed by LAB played an important role in fermentation of rice to produce alcohol and lactic acid (Ghosh et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that consumption of rice beer reduces stress and prevents gastrointestinal infections (Ray et al 2016). Few studies had reported the microbial composition of the starter cake and the biochemical composition of the rice beer (Bhuyan et al 2014;Das et al 2014;Ghosh et al 2015;Sha et al 2017). However, a detailed study on the microbial diversity, their functionalities and the metabolites of rice beer varieties is not yet available to understand their probable effects on health.…”
Section: Introductionmentioning
confidence: 99%